Effect of physical treatment methods for release of inulin from Inula medicinal - Косоголова, Л. О.; Лошицький, П. П.; Уницька, А. Ю.; Чоповська, А. М. (Problems of Environmental Biotechnology, 2017)
The influence of temperature, ultrasound, low frequency radiation 14kHts on the efficiency of extraction of biologically active substance inulin from the roots and rhizomes of medicinal Inula were investigated.